European Television Crime Drama and Beyond (Palgrave European Film and Media Studies, 2018)
This book is the first to focus on the role of European television crime drama on the international market. As a genre, the television crime drama has enjoyed a long and successful career, routinely serving as a prism from which to observe the local, national and even transnational issues that are prevalent in society. This extensive volume explores a wide range of countries, from the US to European countries such as Spain, Italy, the Scandinavian countries, Germany, England and Wales, in order to reveal the very currencies that are at work in the global production and circulation of the TV crime drama. The chapters, all written by leading television and crime fiction scholars, provide readings of crime dramas such as the Swedish-Danish The Bridge, the Welsh Hinterland, the Spanish Under Suspicion, the Italian Gomorrah, the German Tatort and the Turkish Cinayet. By examining both European texts and the 'European-ness' of various international dramas, this book ultimately demonstrates that transnationalism is at the very core of TV crime drama in Europe and beyond. .